ANALISIS HUBUNGAN ANTARA TINGKAT PARTISIPASI PETANI DALAM PENGELOLAAN HUTAN RAKYAT DENGAN KUALITAS HUTAN RAKYAT - Supanggyo Supanggyo (Universitas Sebelas Maret, 2003)
The research objectives were to relation analysis between farmers participation level in private forestry management and qualities at the OYO sub water shed. The research exploited descriptive analysis method, for explanatory the relation between farmers participation level with private forestry and qualities. This research was carried out in the OYO up stream until OYO down stream. The research findings indicated that farmers participation level in privatefore,;try manegement mostly (69,39 %) belonged to high and moderate classification especially plantation activities. The research indicated that the higherfarmers participation level inprivate forestry management. The higher private forest quality that density rate of wood cultivations in the private .forest,y indicated was (r sp 0,67JJ, t cal > t table (a 0,05).